RANCANG BANGUN SISTEM INFORMASI EMPAT DARA KOST BERBASIS WEB DI KOTA BATAM - Andiza, Reno Try; Amrizal, Amrizal (LPPM Universitas Putera Batam, 2021)
Four Dara Kost is a place for lodging services such as boarding houses, but this boarding house only rents rooms, this house has been established since 2010 in the city of Batam. Four Dara Kost have problems in managing their boarding houses sucg as collecting data on prospective occupants, checking rooms and explaining information about boarding room facilities. The researcher aims to help boarding house owners and assistanst on how to desing and implement web-based information systems at the four dara boarding house. Researchers will conduct this research use the waterfall method Results of this research are boarding house owners and boarding house assistants find it easier to process their renting rooms, checking rooms and explaining information on room facilities provided.